Diffusive and non-diffusive language shift: Why are language borders moving and language islands shrinking? - Prochazka, Katharina; Vogl, Gero (Diffusion Fundamentals, 2022)
We compare two situations of language shift: When a language border exists, as e.g. between Slovenian and German in Carinthia, Austria before World War I or between Gaelic and English in Northwestern Scotland, then close to that border language shift is promoted by diffusive contact between different settlements. Such contact, however, was of no significant influence on language shift from German to Hungarian in Southern Hungary where no language border exists.